João do Rio: o repórter com alma de flâneur conduz a crônica-reportagem na Belle Époque tropical - Sousa, Patrícia de Castro (2009)
The research has as its main object parts of João do Rio s writings found in A Alma Encantadora das Ruas (1908). The goal of the research and dissertation herein presented is to investigate the style present in these texts, intending to demonstrate that they represent a interwining transition between a strict literature contribution to a specific jounalistic text: João do Rio would had established the bridge to contemporaneous journalistic writings. The research approach consists in the analysis and classification of selected texts the object under investigation usualy qualified as chronicles by literature experts. However, the relevance of a remarkable journalistic style is found in João do Rio s writings. The chapters of this dissertation add on each other leading to place his writings in the cathegory of chroniclereportage, the concept that motivated the research developed. The investigation encompasses: the writer biography and the background literature influencing him; the historical, social and economical context existing during the first decade of the 20th century, a period during which had appeared a number of writings that contributed to the framing of the interwining components of the journalistic and the literature styles. The flânerie incorporated by João do Rio in his texts and the outcomes of this practice on his writings are analysed in the present dissertation. Furthermore, comments on the stilistics were added demonstrating that the flanêur was not present in the environment he described. The evolution and definitions related to chronicle and reportage are addressed as demanded by the the coexistence of both styles in João do Rio s writings. In addition, the contextual and conceptual components described are step by step followed by a detailed analisys of the investigated object.